Cryosurgery combined with topical interventions for actinic keratosis: a systematic review and meta‐analysis. (27th December 2018) - Heppt, M.V.; Steeb, T.; Ruzicka, T.; Berking, C.
Summary: Background: Actinic keratoses (AKs) are early in situ carcinomas of the skin caused by cumulative sun exposure. Cryosurgery is an easy and practicable lesion‐directed approach for treatment of isolated lesions. Objectives: To investigate whether an upfront combination of cryosurgery with a topical intervention is superior to cryosurgery alone for treatment of AK. Methods: We performed a systematic literature search in MEDLINE, Embase and CENTRAL and hand searched pertinent trial registers for eligible randomized controlled trials until 17 July 2018. Results from individual studies were pooled using a random effects model. The risk of bias was estimated with the Cochrane Risk of Bias Tool and the quality of evidence of the outcomes with the GRADE approach. Results: Out of 1758 records initially identified, nine studies with a total sample size of 1644 patients were included. Cryosurgery in combination with a topical approach showed significantly higher participant complete clearance rates than monotherapy [risk ratio (RR) 1·74, 95% confidence interval (CI) 1·25–2·43, I 2 = 73%, eight studies]. The participant partial clearance rate was not statistically different (RR 1·64, 95% CI 0·88–3·03, I 2 = 77%, three studies). The number of patients who completed the study protocol and did not withdraw due to adverse events was equal in both groups (RR 0·98, 95% CI 0·95–1·01, I 2 = 75%, seven studies). The studies were estimated to have high risk for selective reporting bias. Conclusions: Our results suggest the superiority of a combination regimen for AK clearance, with equal tolerability. This study highlights the importance of a field‐directed approach in patients with multiple AKs or field cancerization. Abstract : What's already known about this topic? Cryosurgery is a fast and easy approach for treatment of isolated actinic keratoses. A variety of effective field‐directed topical interventions are available, but they may lose efficacy in thicker lesions. Combining cryosurgery with a topical intervention offers the benefits of a lesion‐ and field‐directed approach. What does this study add? This meta‐analysis suggests the superiority of a combination of cryosurgery and topical interventions for participant complete clearance, without a difference in tolerability, in comparison with cryosurgery alone. Cryosurgery in combination with a topical intervention is an attractive and effective option for patients with multiple actinic keratoses or field cancerization. Our results highlight the importance of treating the entire actinic field in patients with multiple actinic keratoses. Linked Comment: Dirschka and Gupta. Br J Dermatol 2019; 180 :701 .